Synthesis of some bis-triazole derivatives as probes for cytotoxicity study - Mohammad Al-Amin; M. Rabiul Islam (Bangladesh Pharmacological Society, 2006)
A series of bis[4-N-amino-5-mercapto-1,2,4-triazol-3-yl] alkanes (1a-e) and their Schiff bases with 2-adamanta-none (2a-d) and bis [1, 2, 4-triazolo [3, 4-b] - 1, 3, 4-thiadiazol-4-yl] alkanes (3a-e) have been synthesized with high yields. The cytotoxicity study of these newly synthesized compounds against brine shrimp lethality test as well as Structure-Activity-Relationship (SAR) has been discussed.